The Effect of Vein Viewer Use on the Success of Intravenous Access in Children at the Emergency Unit - Taufiqqurrahman Taufiqqurrahman; Tuti Asrianti Utami; Fulgensius Surianto (Open Access Health Scientific Journal, 2026)
Background: Advanced technological interventions, specifically near-infrared vein visualization devices, have emerged as potential solutions to facilitate real-time vascular observation. This study aimed to analyze the comprehensive effect of utilizing a vein viewer on the clinical success rate of establishing peripheral intravenous access among pediatric patients.Methods: This study employed a descriptive correlational design with a quantitative approach and a retrospective cross-sectional method. The research was conducted at the Emergency Unit of X Hospital, Tangerang, utilizing a total sampling technique that gathered secondary records of 85 pediatric patients aged 0–18 years who underwent peripheral intravenous insertion facilitated by the Vein Viewer Vision 2 device between January and December 2024. Univariate analysis described the frequency distributions of patient age, body weight, procedure duration, and puncture frequency. Bivariate evaluation was executed using the Chi-Square test to evaluate the statistical significance of relationships.Results: First-attempt clinical success in securing peripheral intravenous access reached 68.2%, with the majority of successful procedures completed in less than 10 minutes (68.2%) and requiring exactly one puncture attempt (67.1%). Bivariate statistical testing revealed that pediatric body weight, procedure duration, and the total number of puncture attempts exerted highly significant influences on the final success of intravenous access (p < 0.001). Conversely, the chronological age of the pediatric patients demonstrated no statistically significant correlation with procedural success (p > 0.05).Conclusion: The implementation of near-infrared vein viewer technology significantly sustains high first-attempt insertion success and shortens procedural duration in challenging emergency pediatric cohorts. The device serves as a vital clinical adjunct, particularly for patients with compromised nutritional status or low body weight. Future research should integrate larger multi-center experimental frameworks to expand clinical generalization across diverse pediatric nursing environments.